Hexabromocyclododecanes (HBCDs) in marine fishes along the Chinese coastline - Xia, Chonghuan; Lam, James C.W.; Wu, Xiaoguo; Sun, Liguang; Xie, Zhouqing; Lam, Paul K.S. (Chemosphere (Oxford), 2011)
This study reports concentrations of hexabromocyclododecanes (HBCDs) in two species of marine fish, large yellow croaker (Pseudosciaenacrocea) and silver pomfret (Pampusargenteus) (n=46), from nine Chinese coastal cities (Dalian, Tianjin, Qingdao, Shanghai, Zhoushan, Wenzhou, Fuzhou, Quanzhou and Xiamen). HBCDs were detectable in all samples analyzed, indicating ubiquitous contamination of these compounds in the Chinese coastal environment. The average total HBCD concentration was 3.7ngg−1 lipid weight (range: 0.57–10.1ngg−1 lipid weight), which is relatively lower than other regions of the world, especially Europe, where HBCDs are intensively used. Among the three individual HBCD isomers (α-, β- and γ-HBCD) in all fish samples, the α-isomer showed a remarkable predominance (from 87.5% to 100% of total contribution), indicating its higher bioaccumulative potential. Geographically, the highest HBCD level present in fish was found in Dalian in northern China, and the lowest occurred in Wenzhou. Estimated daily intakes of HBCDs via fish consumption for the Chinese population were 0.004–1.00ngkgbody weight−1d−1. These exposure levels were much lower than the effect levels.